2000
DOI: 10.1080/14616730050085527
|View full text |Cite
|
Sign up to set email alerts
|

Intrusive caregiving and quality of attachment in prenatally drug- exposed toddlers and their primary caregivers

Abstract: The relation between caregiver intrusiveness and the quality of attachment was tested among 51 prenatally drug-exposed toddlers and their primary caregivers. Biological mothers and kinship/foster caregivers neither differed as to caregiver intrusiveness nor as to their toddlers' attachment security and attachment organization. Insecure and disorganized/disoriented attachments were found to be more prevalent in this sample than in normal samples. In keeping with recent findings in non-drug-abusing samples (Isab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 26 publications
7
79
0
1
Order By: Relevance
“…This finding is also in agreement with other studies that report that these types of attachments are related to negative maternal behaviors (Lyons-Ruth et al, 1991). In addition, Swanson (1998) has reported that, for this sample of mothers and their toddlers, disorganized/disoriented attachments are associated with concurrent intrusive maternal behavior at 18 months of age.…”
Section: Caregiving and Attachmentsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is also in agreement with other studies that report that these types of attachments are related to negative maternal behaviors (Lyons-Ruth et al, 1991). In addition, Swanson (1998) has reported that, for this sample of mothers and their toddlers, disorganized/disoriented attachments are associated with concurrent intrusive maternal behavior at 18 months of age.…”
Section: Caregiving and Attachmentsupporting
confidence: 92%
“…As reported in Swanson (1998), there was a significant increase in the proportion of disorganized/disoriented attachments in this sample compared to normative populations. This finding is in agreement with Rodning et al (1991), who reported similar elevated rates of disorganized/ disoriented attachments among a sample of PCP-abusing women and their offspring.…”
Section: Caregiving and Attachmentsupporting
confidence: 43%
See 2 more Smart Citations
“…The EA Scales have been used with children from both low and high social-risk populations (e.g., Oyen, Landy, & Hilburn-Cobb, 2000;Swanson, Beckwith, & Howard, 2000). More complete descriptions of the EA Scales can be found in Biringen and Robinson (1991), Biringen (2000), and Easterbrooks and Biringen (2000, 2005.…”
Section: Data Coding and Scoringmentioning
confidence: 99%